Risk Factors Of Hypertension In The Elderly In The Public Health Center Siulak Gedang Kerinci Regency in 2022 - Annisa Novita Sary; Ika Yulia Darma; Natasya Risa Putri; Eliza Trisnadewi; Wiya Elsa Fitri; Edison Edison (Stikes Syedza Saintika Padang, 2022)
ABSTRACT There has been an expansion in the rate of hypertension in the older over the most recent three years.The study's objective was to ascertain the factors associated with the prevalence of hypertension among elderly people in the Siulak Gedang Health Center's working area in the Kerinci Regency in 2022. This study uses an observational analytic approach with a case-control research design. The study was conducted at the Siulak gedang Kerinci District Health Center in July-September 2022. using an accidental sampling technique, with the number of samples as high as 54 people for the case group and the control group with regard to individual gender matching. The univariate and bivariate chi-square tests were used to analyze the data. The results showed that less than half of respondents with hypertension who smoke (22.2%) and non-hypertensive respondents who smoke (24.1%), more than half of respondents with hypertension are overweight (70.4%), less than half of respondents without hypertension are overweight (46.3%), and more than half of respondents with hypertension have less physical activity (64.8%), and less than half of respondents without hypertension have less physical activity (42.6%). The results of bivariate analysis showed that there is no relationship between smoking habits (p=1,000; OR= 0,901 ; 95% CI 0,368–2,205); there is a relationship between excess body weight (p= 0,019; OR= 2,755; 95% CI 1,248–6,083) and physical activity (p= 0,034; OR= 2,483; 95% CI 1,142–5,397) with the elderly in the working area of Puskesmas siulak Gedang Kerinci regency in 2022. From the results of the study, it can be concluded that overweight and physical activity are risk factors for the occurrence of hypertension in the elderly. It is expected that the elderly regularly do physical activity to prevent overweight and hypertension.